Elastoplastic deformation of two phase steels studied by neutron diffraction and self-consistent modelling - Daymond, M; Priesmeyer, H; Korsunsky, A (Springer International Publishing AG, 2002)
In situ neutron diffraction experiments allow the measurement of phase specific strain, and thus stress, in a multi-phase system. Further, monitoring of multiple hkl lattice planes provides information as to the response of differently oriented grains within the polycrystal. These experimental results can be compared directly with predictions from a self-consistent Hill-Hutchinson model modified to take into account the presence of the second phase. The techniques and ideas are demonstrated with recent tests on two practical engineering steels (1) ferritic steel, with a small volume fraction of carbon in the form of cementite and (2) duplex steel, consisting of approximately equal amounts of austenitic and ferritic phases. Good qualitative agreement was obtained between model and experimental data in each case. Issues affecting the use of such a model for two phase systems are discussed. The interpretation of residual stress measurements, for both single and peak and Rietveld multi-peak measurements is considered.